1992
DOI: 10.1007/bf02207197
|View full text |Cite
|
Sign up to set email alerts
|

Thermography of frozen shoulder and rotator cuff tendinitis

Abstract: The role of thermography in the diagnosis of soft tissue lesions of the shoulder was evaluated by screening 28 patients with unilateral frozen shoulder and 86 patients with unilateral rotator cuff lesions. Index shoulders were then compared with the normal side. Differences in skin temperature distribution were found in 82% of subjects with frozen shoulder, nearly three-quarters of whom had reduced skin temperature. There was no consistent pattern of shoulder skin temperature found in rotator cuff tendinitis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…They concluded that these abnormalities clearly suggested a sympathetic dysfunction in the dermatome subserving pain sensation from the affected shoulder. Vecchio et al 19 reported that differences in skin temperature distribution were found in 82% of subjects with adhesive capsulitis, and nearly 75% of these subjects had reduced skin temperatures. They also studied patients with rotator cuff tendinitis but found no consistent patterns in shoulder skin temperatures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They concluded that these abnormalities clearly suggested a sympathetic dysfunction in the dermatome subserving pain sensation from the affected shoulder. Vecchio et al 19 reported that differences in skin temperature distribution were found in 82% of subjects with adhesive capsulitis, and nearly 75% of these subjects had reduced skin temperatures. They also studied patients with rotator cuff tendinitis but found no consistent patterns in shoulder skin temperatures.…”
Section: Discussionmentioning
confidence: 98%
“…14 Thermography is rarely used for the assessment of shoulder disorders, although some investigators have studied adhesive capsulitis in the past. 13,19 Jeracitano et al 13 found that patients with adhesive capsulitis displayed an abnormal temperature response. They concluded that these abnormalities clearly suggested a sympathetic dysfunction in the dermatome subserving pain sensation from the affected shoulder.…”
Section: Discussionmentioning
confidence: 98%
“…Sherman et al (1995) did not find thermographic asymmetry in the lower extremities of new army recruits to be predictive of later limb pain or as a basis for diagnosis in this young, healthy male population. In comparison with their asymptomatic side, three-quarters of tested patients with frozen shoulder had abnormally cold symptomatic shoulders, whereas, for rotator cuff tendinitis, 28% showed abnormally cold and 23% had abnormally warm shoulders (Vecchio et al 1992). Symptom severity was not noted in the above studies.…”
Section: Introductionmentioning
confidence: 92%
“…Local skin temperature can be used to monitor and detect inflammation associated with knee replacement (Haidar et al, 2006;Mehra et al, 2005), rheumatoid arthritis (Rajapakse et al, 1981), osteoarthritis (Denoble et al, 2010), allergies (Rokita et al, 2011), frozen shoulder (Vecchio et al, 1992) and even tendinitis (Miyakoshi et al, 1998). Mean skin temperature on the other hand, is most commonly used as an important component of overall thermal stress (Frim et al, 1990), thermal comfort (International Organisation for Standardisation, 2004) and in the calculation of mean body temperature (Colin et al, 1971).…”
Section: Introductionmentioning
confidence: 99%